The repeated cytogenetic analysis of subjects occupationally exposed to nanoparticles: a pilot study - Rossnerova, Andrea; Pelclova, Daniela; Zdimal, Vladimir; Rossner, Pavel; Elzeinova, Fatima; Vrbova, Kristyna; Topinka, Jan; Schwarz, Jaroslav; Ondracek, Jakub; Kostejn, Martin; Komarc, Martin; Vlckova, Stepanka; et al. (Mutagenesis, 2019)
The application of nanomaterials has been rapidly increasing during recent years. Inhalation exposure to nanoparticles (NP) may result in negative toxic effects but there is a critical lack of human studies, especially those related to possible DNA alterations. We analyzed pre-shift and post-shift a group of nanocomposite researchers with a long-term working background (17.8 ± 10.0 years) and matched controls. The study group consisted of 73.2% males and 26.8% females. Aerosol exposure monitoring during a working shift (involving welding, smelting, machining) to assess the differences in exposure to particulate matter (PM) including nanosized fractions <25-100 nm, and their chemical analysis, was carried out. A micronucleus assay using Human Pan Centromeric probes, was applied to distinguish between the frequency of centromere positive (CEN+) and centromere negative (CEN-) micronuclei (MN) in the binucleated cells. This approach allowed recognition of the types of chromosomal damage: losses and breaks. The monitoring data revealed differences in the exposure to NP related to individual working processes, and in the chemical composition of nanofraction. The cytogenetic results of this pilot study demonstrated a lack of effect of long-term (years) exposure to NP (total frequency of MN, P = 0.743), although this exposure may be responsible for DNA damage pattern changes (12% increase of chromosomal breaks-clastogenic effect). Moreover, short-term (daily shift) exposure could be a reason for the increase of chromosomal breaks in a subgroup of researchers involved in welding and smelting processes (clastogenic effect, P = 0.037). The gender and/or gender ratio of the study participants was also an important factor for the interpretation of the results. As this type of human study is unique, further research is needed to understand the effects of long-term and short-term exposure to NP.
Keywords: mutageny; pevné částice; Nanoparticles; Micronucleus Tests; mikrojaderné testy; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Mutagens; cytogenetické vyšetření; Young Adult; ženské pohlaví; Occupational Exposure; Humans; pracovní expozice; pilotní projekty; Particulate Matter; nanočástice; lidé středního věku; Cytogenetic Analysis; Pilot Projects; dospělí; Female; lidé; Male